Reconstructing Da’wah of Salafi in Shaikh Muhammad Al-Ghazali Works - Dindin Solahudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
Salafism has developed into different interpretations and understandings. Every da’wah movement claims to follow Salafi way of its own interpretation. This study aims at portraying one of Salafi understandings and its Salafi da’wah. This research used literature review to reconstruct the model of first emerging da’wah according to Shaikh Muhammad Al-Ghazali, a 20th century da’wah thinker and practicioner. It used his works that are supposed to bear objective, original views, and understanding on Salafism and Salafi da’wah. The study shows that since the time of the prophet the core characteristics of Salafi da’wah are criticism, constructivism, and moderation. Salafisme telah berkembang menjadi beragam interpretasi dan pemahaman. Setiap gerakan dakwah mengklaim mengikuti cara Salafi dalam interpretasinya. Penelitian ini bertujuan untuk menggambarkan salah satu pemahaman Salafi dan dakwah Salafi. Penelitian ini menggunakan analisis literatur untuk merekonstruksi model pertama kemunculan dakwah menurut Shaikh Muhammad Al-Ghazali, seorang pemikir dan praktisi dakwah abad ke-20. Ia menggunakan karya-karyanya yang seharusnya memiliki pandangan objektif, asli, dan pemahaman tentang Salafisme dan dakwah Salafi. Studi ini menunjukkan bahwa sejak masa nabi, karakteristik inti dari dakwah Salafi adalah kritis, konstruktivisme, dan moderasi.